Legal and legislative study of biological objects be withdrawn from human corpse for scientific research in anatomy, histology, cytology. - Mishalov, V. D.; Tverdokhlib, I. V.; Yurchenko, V. T. (Морфологія / Morphologia / Morfologìâ, 2016)
Based on the analysis of changes in the new edition of the Criminal Procedural Code of Ukraine (2012) in combination with other applicable regulations, applicable to the forensics and legal status of the person who died, reasonable legal and legislative capabilities withdrawal (registration) parts of the body, organs and tissues, blood or other biological materials for scientific research in human anatomy, histology and cytology.